The sisters Weiss - Ragen, Naomi, 1949- (St. Martin's Griffin, 2014)
In 1950's Brooklyn, sisters Rose and Pearl Weiss grow up in a loving but strict ultra-Orthodox Jewish family, never dreaming of defying their parents or their community's unbending and intrusive demands. Then, a chance meeting with a young French immigrant turns Rose's world upside down, its once bearable strictures suddenly tightening like a noose around her neck. Defiantly, she begins to live a secret life that shocks her family when it is discovered. Out of guilt and an overwhelming desire to be reconciled with those she loves, she finally bows to her parents' demands that she agree to an arranged marriage. But the night before her wedding, she commits an act of defiance so unforgivable it will exile her forever from her innocent young sister, her family, and all she has ever known. Forty years later, pious Pearl's sheltered young daughter Rivka suddenly discovers the truth about the family outcast, her Aunt Rose, now a successful photographer. Inspired, but naive and reckless, she sets off on a dangerous adventure that will stir up the ghosts of the past and alter the future in unimaginable ways for all involved.